Extremely low-frequency electromagnetic fields facilitate proliferation and functional differentiation in spinal neural stem cells - Wenxu Tang; Dan He; Xiaofei Li; Yi Feng; Yue Xu; Jiawei Hu; Wei Xu; Lei Xue (Scientific Reports)
Abstract Traumatic spinal cord injury (SCI), typically resulting from direct mechanical damage to the spine, often leads to disruption of neural signaling and axonal conduction, severely impairing nervous system function. In rodent models of SCI, neural stem cell (NSC) transplantation has demonstrated significant potential in restoring motor function and enhancing neural repair. Additionally, extremely low-frequency electromagnetic fields (ELF-EMFs) have demonstrated efficacy in promoting nerve regeneration and activating spinal circuits. However, studies exploring how ELF-EMFs influence NSC activation remain limited. In this study, using spinal cord-derived NSCs from adult mice, we report that ELF-EMFs enhance cell proliferation and self-renewal by upregulating Sox2 expression. Furthermore, we addressed the underlying mechanisms and found that ELF-EMFs activate T-type calcium channels and enhance calcium currents. The resulting increase in intercellular calcium concentration upregulates the expression of NeuroG1 and NeuroD1, promoting neuronal differentiation of NSCs and enhancing neurite outgrowth. Our findings provide new insights into the ELF-EMF-mediated activation of NSCs and highlight their potential for integration into combination therapies and SCI repair.